The Relationship between Social Supports with Nursing Employee Attachment at Dr. R.M. Djoelham Hospital Binjai - Nini Sri Wahyuni; Rahma Fauzia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This article deals with the relationship between social supports with nursing employee attachment at Dr. R.M. Djoelham Hospital Binjai. This study aims to see the relationship between two variables and in the process of data analysis. This study uses numerical data or numbers that are processed by methodology, after the results are obtained then described by outlining the conclusions based on the numbers with the statistical method. The results shows that there is a significant positive relationship between social support and work attachment. This result is proven by the correlation coefficient  = 0.377; p = 0.000 means p <0.010 means that the higher the social support, the higher the attachment of work to nurses and vice versa, if social support is obtained low, then the attachment of nurses work is also low. Thus, the hypothesis that has been proposed in this research is accepted. Social support has an effect of 14.2% on work attachment known from the determinant coefficient = 14.2%. There are still 85.8% influence from other factors that affect work attachment, namely compensation, skills, optimism, self efficacy, and reciliency.